Evolution of scientific views on the place and role of cost management in enterprise management - Ван, Цзяньбо (БНТУ, 2025)
The article is devoted to the study of the evolution of scientific views on the place and role of cost management in enterprise management. Generalization of modern Chinese and English-language literature allowed the author to highlight the following approaches to the interpretation of the term ՙՙcost management՚՚: traditional, optimization, strategic and administrative-controlling. Each of these approaches is characterized substantively: its adherents are listed, the reasons for its emergence, strengths and weaknesses are identified. The author's definition of the concept of "cost management" is proposed, the novelty of which lies in the following: cost management is not limited to financial management (managerial, accounting, tax accounting); cost management is linked to the business strategy of enterprise development, while not being identified with it, that is, it is considered as one of its tools; cost management is not limited to intra-firm relations and is formed, among other things, under the influence of external factors (industry, macroeconomic, international); cost management is not limited to reducing them, but is considered as a process of ranking them in accordance with business strategy; the cost management process is considered dynamically, as a continuously repeating cycle of forecasting, accounting, control and adjustment; the goal of cost management is defined not as profit maximization, but as increasing the development potential of the enterprise and creating a basis for its long-term development.
Эволюция научных взглядов на место и роль управления затратами в управлении предприятием